PENGARUH KEPUASAN KERJA TERHADAP PROXIMAL WITHDRAWAL STATES PADA KARYAWAN PERUSAHAAN PERBANKAN - Venesia, Venesia; Tumanggor, Raja O.; Suyasa, P. Tommy Y.S. (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2020)
Banks play an important role in a country's economy. However, banks face various challenges in meeting their objectives. One of the challenges faced by some banks is a high employee turnover rate. In regards to turnover, there is a new concept of proximal withdrawal states proposed by Hom, Mitchell, Lee, and Griffeth (2012) as the closest and more accurate predictor of turnover than intention to leave (Li, Lee, Mitchell, Hom, & Griffeth, 2016).Proximal withdrawal states is the condition of one's motivation towards the company where he/she works, which consists of two dimensions, namely (a) preference to leave or stay in the company (intention to leave) and (b) control of those desires (perceived control over preference). The combination of the two dimensions forms four types of proximal withdrawal states, namely enthusiastic leavers, reluctant stayers, reluctant leavers, and enthusiastic stayers. Job satisfaction, which has a significant negative relationship with intention to quit (Masum et al., 2016), proved to be more accurate in predicting turnover when analyzed with proximal withdrawal states (Li et al., 2016).This study aims to determine the effect of job satisfaction on proximal withdrawal states in banking company employees. This study uses descriptive non-experimental research method, with purposive sampling technique. 273 banking company employees who participated in this study. The results of the analysis using multinominal logistic regression testing showed the effect of job satisfaction on proximal withdrawal states for banking employees. The higher the level of job satisfaction of banking employees, the greater the tendency for employees to become enthusiastic stayers or reluctant stayers, both of whom have a desire to remain in the company. Bank memiliki peran penting bagi perekonomian negara. Namun bank menghadapi berbagai tantangan dalam memenuhi tujuannya. Salah satu tantangan yang dihadapi beberapa bank adalah tingkat turnover karyawan yang tinggi. Terkait dengan turnover, terdapat konsep baru mengenai proximal withdrawal states yang diusulkan oleh Hom, Mitchell, Lee, dan Griffeth (2012) sebagai faktor (prediktor) yang paling dekat dan lebih akurat untuk memprediksi turnover dibandingkan intention to leave (Li, Lee, Mitchell, Hom, & Griffeth, 2016). Proximal withdrawal states adalah kondisi motivasi seseorang terhadap perusahaan di mana ia bekerja, yang terdiri dari dua dimensi yaitu (a) preferensi untuk keluar atau menetap di perusahaan (intention to leave) dan (b) kendali atas keinginan tersebut (perceived control over preference). Perpaduan kedua dimensi tersebut membentuk empat jenis proximal withdrawal states, yaitu enthusiastic leavers, reluctant stayers, reluctant leavers, dan enthusiastic stayers. Kepuasan kerja, yang memiliki hubungan signifikan negatif dengan intention to quit (Masum et al., 2016), terbukti semakin akurat dalam memprediksi turnover ketika dianalisis dengan proximal withdrawal states (Li et al., 2016). Penelitian ini bertujuan mengetahui pengaruh kepuasan kerja terhadap proximal withdrawal states pada karyawan perusahaan perbankan. Penelitian ini menggunakan metode penelitian non eksperimental deskriptif, dengan teknik purposive sampling. Terdapat 273 karyawan perusahaan perbankan yang menjadi partisipan dalam penelitian ini. Hasil analisis dengan pengujian regresi logistik multinominal menunjukkan adanya pengaruh kepuasan kerja terhadap proximal withdrawal states pada karyawan perbankan. Semakin tinggi tingkat kepuasan kerja karyawan perbankan, maka semakin besar peluang karyawan untuk menjadi enthusiastic stayers ataupun reluctant stayers, di mana keduanya memiliki keinginan untuk menetap di perusahaan.